Rancang Bangun Sistem Informasi Pengelolaan Penelitian Dosen Menggunakan Metode Prototyping - Moh Erkamim; Vera Wati; Wartono Wartono; Farid Fitriyadi (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
LPPM UTP Surakarta is an institution in charge of planning, coordinating, monitoring, and conducting assessments in research activities and lecturer service in the campus environment. However, at this time, both delivery and administrative management are still conventional by sending proposal files by coming to the institution. Notification of the status of proposal submissions being accepted for funding or not is still being informed to the faculty of each study program, where sometimes the information does not reach the proposer directly. So to summarize the activities of submitting and managing proposals, of course, requires a system that involves technology. The web-based LPPM research and community service management information system is one solution that can be used to help manage research and community service with university funding sources. Currently, the management of activity funds sourced from universities refers to the provisions set by universities and the process of managing this proposal selection does not yet use an information system that is easily accessible by related parties. It is necessary to develop a systematic and transparent system, one solution is to use a research and service management information system. The design of the information system uses a web-based prototyping approach, where this method has a clear picture before the system enters the development process, it is illustrated with an interface display so that the functionality meets the criteria and is quickly understood by the user. Features in this system include login access rights, submission process, proposal management, and review information so that the proposal submission status process can be monitored through the system in real-time. The results of system testing with black box testing carried out by 3 LPPM UTP managers and 2 system developers resulted in a 100% functionality value indicating the results were as expected.